2017
DOI: 10.1182/blood-2016-10-692400
|View full text |Cite
|
Sign up to set email alerts
|

Splicing factor gene mutations in hematologic malignancies

Abstract: Alternative splicing generates a diversity of messenger RNA (mRNA) transcripts from a single mRNA precursor and contributes to the complexity of our proteome. Splicing is perturbed by a variety of mechanisms in cancer. Recurrent mutations in splicing factors have emerged as a hallmark of several hematologic malignancies. Splicing factor mutations tend to occur in the founding clone of myeloid cancers, and these mutations have recently been identified in blood cells from normal, healthy elderly individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 117 publications
(131 reference statements)
2
108
0
Order By: Relevance
“…Mutations lie within hotspots (codons 662, 666, 700, 704, 742), with codon 700 harbouring 50% of the mutations, and affect the C‐terminal HEAT‐repeat region of the protein. SF3B1 mutations promote the use of alternative branch point based on their greater (with respect to the regular ones) complementarity to the U2 snRNA, leading to the inclusion of 3′ intronic sequences in the mature RNA (Darman et al , ; Alsafadi et al , ; Kesarwani et al , ; Saez et al , ). It was suggested that SF3B1 mutations increase NOTCH signalling via alternative splicing of a negative regulator of NOTCH signalling, DVL2 (Wang et al , ).…”
Section: Mutations Affecting the Rna Processing Pathwaymentioning
confidence: 99%
“…Mutations lie within hotspots (codons 662, 666, 700, 704, 742), with codon 700 harbouring 50% of the mutations, and affect the C‐terminal HEAT‐repeat region of the protein. SF3B1 mutations promote the use of alternative branch point based on their greater (with respect to the regular ones) complementarity to the U2 snRNA, leading to the inclusion of 3′ intronic sequences in the mature RNA (Darman et al , ; Alsafadi et al , ; Kesarwani et al , ; Saez et al , ). It was suggested that SF3B1 mutations increase NOTCH signalling via alternative splicing of a negative regulator of NOTCH signalling, DVL2 (Wang et al , ).…”
Section: Mutations Affecting the Rna Processing Pathwaymentioning
confidence: 99%
“…RNA binding proteins (RBPs) interact with their target RNAs to affect the creation, localization, and function of each RNA molecule in the cell . Disruption of these protein–RNA interactions by mutations in RBPs has been implicated in many diseases including neurodegeneration and cancer . Therefore, identifying the RNA targets of specific RBPs is important for deciphering the molecular mechanisms of RBP‐mediated diseases.…”
Section: Introductionmentioning
confidence: 99%
“…8, [23][24][25] Although there have been major advances in understanding the role of RNA splicing factor mutations in MDS pathogenesis and therapy (as reviewed recently [26][27][28] ), major questions about their biological consequences within cells, requirement in disease initiation vs maintenance, and cell autonomous vs nonautonomous roles remain. In addition, numerous questions about the structural and biochemical effects of the mutations on protein-protein and protein-RNA interactions.…”
Section: Introductionmentioning
confidence: 99%